2013
DOI: 10.1002/jor.22355
|View full text |Cite
|
Sign up to set email alerts
|

Needle puncture injury causes acute and long-term mechanical deficiency in a mouse model of intervertebral disc degeneration

Abstract: Low back pain is a significant socioeconomic burden and intervertebral disc degeneration has been implicated as a cause. A reliable animal model of disc degeneration is necessary to evaluate therapeutics, and functional metrics are essential to quantify their benefit. To this end, needle puncture injuries were created in the caudal intervertebral discs of mice to induce disc degeneration. Compression, torsion, and creep mechanics were assessed both immediately and after eight weeks to distinguish between the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
136
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(142 citation statements)
references
References 30 publications
6
136
0
Order By: Relevance
“…Opposing, in mice, the caudal disc puncture with a small gauge needle (29-gauge) did not initiate degenerative changes in disc structure and composition 4 . Since our group and others, have regularly used the 30-gauge needle for intradiscal injection of innocuous or potential therapeutic compounds, our aim was to investigate if this procedure could trigger observable changes on intervertebral disc.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Opposing, in mice, the caudal disc puncture with a small gauge needle (29-gauge) did not initiate degenerative changes in disc structure and composition 4 . Since our group and others, have regularly used the 30-gauge needle for intradiscal injection of innocuous or potential therapeutic compounds, our aim was to investigate if this procedure could trigger observable changes on intervertebral disc.…”
Section: Introductionmentioning
confidence: 91%
“…Among others, the degenerative process induced by needle puncture has gained popularity because it is uncomplicated, reproducible, and cost-effective, and requires a short time to produce the disc degeneration [2][3][4] . While human disc degeneration is a complex and multifactorial process that occurs over decades, the limited anular injury induced by needle puncture is a potential initiator of disc degeneration 2,3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(200)(201)(202)(203) Increased production of cytokines, particularly TGF-b favors these transformations. (203)(204)(205) The NP contains MSC that are similar to the MSC recovered from bone marrow (206), and studies in animal models of DD have shown that MSC injected in the NP area not only survive for months but also proliferate in canine (207,208), porcine (209), and rabbit models (210). Moreover, the transplanted MSC induced production of extracellular matrix proteins, including aggrecan and other proteoglycans, and types I and II collagens.…”
Section: Lbp Pathophysiologymentioning
confidence: 99%
“…Moreover, the transplanted MSC induced production of extracellular matrix proteins, including aggrecan and other proteoglycans, and types I and II collagens. (207,209,210) A major limitation of using stem cells as a therapy for IDD is an appropriate delivery method that will not cause further injury to the IVD. The most direct route is an injection into the affected IVD, ensuring a localized therapeutic effect.…”
Section: Lbp Pathophysiologymentioning
confidence: 99%